Preparation of Different Carbon Materials by Thermochemical Conversion of Lignin - Rosas, Juana M.; Berenguer, Raúl; Valero-Romero, María José; Rodríguez-Mirasol, José; Cordero, Tomás (Frontiers in Materials, 2014)
Lignin valorization plays a crucial role within the modern biorefinery scheme from both the economic and environmental points of view; and the structure and composition of lignin makes it an ideal precursor for the preparation of advanced carbon materials with high added-value. This review provides an overview of the different carbonaceous materials obtained by thermochemical conversion of lignin, such as activated carbons, carbon fibers, templated carbons, and high ordered carbons, giving information about the new strategies in terms of the preparation method and their possible applications.